Formation Of Science as A Value and Classification of Values - Akbarov Anvar Tojimatovich; Ubaydullayev Saidakbar Saydaliyevich (Zien Journals, 2021)
The article examines the views of the formation of science as a value, the views of researchers in this regard. Values and their classification are also given
Keywords: Value; classification of values; science; phenomenon; quality